Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.adolescence.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Open up or close down: How do parental reactions affect youth information management?☆

Abstract: The purpose of this study was to test a process model of youths' information management. Using three waves of longitudinal data collected from 982 youths, we modeled parents' positive and negative reactions to disclosure predicting youths' feelings about their parents, in turn predicting youths' disclosure and secrecy about their daily activities. Gender, age, and psychopathic personality traits were examined as potential moderators. The results showed that parents' negative reactions were associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
206
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(236 citation statements)
references
References 59 publications
(78 reference statements)
18
206
3
2
Order By: Relevance
“…In addition to the parental negative reactions identified in previous research (Kerr et al, 1999;Marshall et al, 2005;Tilton-Weaver et al, 2010), new forms of parental behavior which play a role in facilitating adolescent disclosure have been introduced in the PBAD-A (i.e. creating opportunities for adolescent's disclosure, asking unobtrusive questions, parental own disclosure) and PBAD-R (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the parental negative reactions identified in previous research (Kerr et al, 1999;Marshall et al, 2005;Tilton-Weaver et al, 2010), new forms of parental behavior which play a role in facilitating adolescent disclosure have been introduced in the PBAD-A (i.e. creating opportunities for adolescent's disclosure, asking unobtrusive questions, parental own disclosure) and PBAD-R (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Five-point response scales were used (1-never to 5-always). Several studies found a two-factor structure of the scale: disclosure and secrecy (Frijns, Keijsers, Branje, & Meeus, 2010;Tilton-Weaver et al, 2010), pointing out the importance of conceptually distinguishing between the two. Since it is not yet clear whether this structure stems from conceptual difference between disclosure and secrecy or it represents a disclosure topic specificity (disclosure items concern school and friends; secrecy items concern free time, nights and weekends), we rephrased the two secrecy items to measure disclosure (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For youths high on CU traits, parents may have to rely more on what the youth feels like disclosing. Indeed, youths with CU traits are possibly least likely to freely give information to their parents [33], and parents might be responding to this closed behavior by reducing their monitoring attempts.…”
Section: Testing the Effect Of Youth Characteristics On The Two Modelsmentioning
confidence: 99%
“…Although adolescents may employ a range of different strategies (Cumsille, Darling, & Martinez, 2010;Marshall et al, 2005), previous work suggests that information management strategies can be classified efficiently as concealing strategies or revealing strategies (e.g., . Concealing and revealing are not two opposite ends of the same continuum Larson & Chastain, 1990), but represent distinct types of strategies, with their own outcomes and precursors (Cumsille et al, 2010;Marshall et al, 2005;Tilton-Weaver et al, 2010). Therefore, both disclosure (a revealing strategy) and secrecy (a concealing strategy) were assessed in the current study.…”
Section: Conceptualization Of Parental Monitoring and Adolescent Infomentioning
confidence: 99%